Individual life premium system - Mupotaringa, Emmanuel (Midlands State University, 2019)
The nature of business is based on overpowering the firm’s opponents so to acquire high yield in all fields involved. Interviews, observation and questionnaires were the gears used in collecting the essential data with the aim of trying to observe how the modern system worked. This system targets at helping Zimnat Premium Policy clients in getting accredit premium payoffs and replaces the manual processes involved in the collection of client details and capturing transactions. The cashier has the access to the premium payment procedures and the rest of the users at the firm can participate in the chatting platform. Some of the tools which were used to come up with this system involved PHP and MySQL, mostly in the Databank designing. After a thorough analysis and the actual creation of the system, the scheme was introduced using the direct changeover approach. However, it is greatly and highly recommended to proceed with the upgrading of the system, so to add features which would in-turn benefit the firm’s customers and the management so to properly manage its commodities.